Fire response of the endangered Pinus culminicola stands after 18 years in Cerro El Potosí, northeast Mexico - Arévalo Sierra, José Ramón; Estrada, Eduardo; Encina, Juan A.; Villarreal, José A.; Escobedo, Job R.; Morales, Yaretzi; Cantú, Israel; González Rodríguez, Humberto; Uvalle Sauceda, José Isidro (2017)
Abstract Aim of the study: To analyze the impact of the 1998 wildfire on dwarf pine (Pinus culminicola) population stands 18 years after the fire. Area of study: Cerro el Potosí, Nuevo León (México). Material and methods: We measured regeneration, biovolume of individuals, diversity and species composition in unburned and burned plots randomly selected in the area. Main results: Recovery was very slow, with limited dense natural regeneration and very slow growth. Significant differences between control and burned plots were found with respect to regeneration, species composition, evenness and soil nutrients, suggesting that fire could promote natural regeneration and biodiversity in these communities. Research highlights: Management efforts are necessary to maintain a natural fire regime and ensure grazing exclusion in order to favor the conservation of the community dominated by this rare species P. culminicola. Additional keywords: fire ecology; DCA; Permanova; richness. Abbreviations used: CIC (Cationic Interchange Complex); DCA (Detrended Correspondence Analysis); EC (Exchangeable Cation); OM (Organic Matter). Authors´ contributions: Conceived, designed and performed the experiments: JRA, EE and HGR. Analyzed the data: JRA, JAV, JRE and YM. Contributed reagents/materials/analysis tools: JAV, JRE, YM, IC and JU. Wrote the paper: JRA, JAE and EE. All authors read and approved the final manuscript. Citation: Arévalo, J. R.; Estrada, E.; Encina, J. A.; Villarreal, J. A.; Escobedo, J. R.; Morales, Y.; Cantú, I.; González-Rodríguez, H.; Uvalle, J. (2017). Fire response of the endangered Pinus culminicola stands after 18 years in Cerro El Potosí, northeast Mexico. Forest Systems, Volume 26, Issue 3, e015. https://doi.org/10.5424/fs/2017263-11566 Received: 20 Apr 2017. Accepted: 21 Nov 2017. Copyright © 2017 INIA. This is an open access article distributed under the terms of the Creative Commons Attribution (CC-by) Spain 3.0 License. Funding: Program of cooperation Universidad de La Laguna-Universidad Autónoma de Nuevo León, included in the official frame agreement of these institutions; Facultad de Ciencias Forestales of the Universidad Autónoma de Nuevo León; University of La Laguna (Research Program) covered the travel expenses of JRA. Competing interests: The authors have declared that no competing interests exist. Correspondence should be addressed to José R. Arévalo: jarevalo@ull.edu.es